2013
DOI: 10.1007/s11832-012-0458-3
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic scoliosis: Etiological concepts and hypotheses

Abstract: Scoliosis is diagnosed as idiopathic in 70 % of structural deformities affecting the spine in children and adolescents, probably reflecting our current misunderstanding of this disease. By definition, a structural scoliosis should be the result of some primary disorder. The goal of this article is to give a comprehensive overview of the currently proposed etiological concepts in idiopathic scoliosis regarding genetics, molecular biology, biomechanics, and neurology, with particular emphasis on adolescent idiop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 68 publications
0
32
0
4
Order By: Relevance
“…In another study, serum copper and zinc levels were found to be normal in IS patients [13]. In a different study conducted by Dastych et al, copper levels in the back muscles of IS patients were found to be low, but no significant difference was found in hair, leucocyte, and serum compared to the control group [26].…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…In another study, serum copper and zinc levels were found to be normal in IS patients [13]. In a different study conducted by Dastych et al, copper levels in the back muscles of IS patients were found to be low, but no significant difference was found in hair, leucocyte, and serum compared to the control group [26].…”
Section: Discussionmentioning
confidence: 86%
“…In some studies, serum selenium levels were found to be low in the scoliosis patients [10,13,14]. In a study for example, selenium levels both in the serum and in hair samples were found to be low in IS patients [14].…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations